(untitled) (Teras, 2021)
Water is one of the main resources for the needs of human life in this universe. Provision of proper sanitation facilities depends on the availability of adequate drinking water facilities. The problem of meeting the need for clean water requires serious attention from the government and the community, one of the government programs in the provision of clean water and sanitation is PAMSIMAS, which is a program carried out by the government to help raise public awareness in the provision of clean water and overcome community-based sanitation problems, especially rural communities. and suburbs. In a water distribution there must be obstacles in water loss. This study focuses on knowing how much water discharge and water loss is in 10 villages that have been installed with the PAMSIMAS program in Jepara Regency, namely the villages of Klepu, Jugo, Sumberrejo, Kepuk, Bracelet, Damarwulan, Bucu, Sumanding, Tunahan, and Dudakawu. To continue to meet the need for clean water, the PAMSIMAS clean water supply system is also planned to meet the needs until 2040. The results showed that the highest water loss was in Bucu village at 61.0% and the lowest was in Klepu, Jugo, Sumberejo, and Damarwulan villages at 6.25. %. The highest water discharge was found in the villages of Gelang and Sumanding at 24.5 m3/second and the lowest in the village of Jugo at 8.57 m3/second. The results of the simulation of the pipeline network using the Epanet 2.0 program, the design criteria for the pipeline network are able to meet the needs of clean water in each village. The source water debit is able to meet domestic water needs until 2040. The inhibiting factors for the PAMSIMAS program are broken pipes due to vehicles, landslides, fires in the dry season, and damaged meters. While the supporting factor that has not been implemented is the absence of a reservoir for excessive water sources.